Mineral reference intervals in confined swine with different genetic background and categories (FAVE Sección Ciencias Veterinarias, 2017)
In Argentina, there is no regional data on mineral reference intervals in swine, according to the genetic lines, categories of production in intensive systems. The objective of this study was to establish ranges of the following serum minerals: calcium, phosphorus, magnesium, sodium, potassium, iron, copper and zinc, in swine farmed in Santa Fe and Entre Ríos. Blood samples were collected from 300 healthy pigs of two different genetic lines belonging to the following categories: newborn piglets, weaned piglets, pregnant nulliparous females selected for re-stocking, and pregnant multiparous females. Serum concentrations of minerals were determined by atomic absorption spectrophotometry (FAAS) with a Perkin Elmer model Analys 200 and using official AOAC methods. Water samples were also analyzed. Reference intervals were calculated using parametric or nonparametric methods on basis of data distribution. Mean, median, minimum, maximum values and reference intervals for different minerals were tabulated. The reference intervals calculated in this study will be useful for the diagnosis of mineral deficiencies and nutritional monitoring in meat production pigs.
Keywords: swine; minerals; productive stages; genetic lineages; Argentina